Fluid flow and water–rock interaction across the active Nankai Trough subduction zone forearc revealed by boron isotope geochemistry. (15th November 2016) - Hüpers, Andre; Kasemann, Simone A.; Kopf, Achim J.; Meixner, Anette; Toki, Tomohiro; Shinjo, Ryuichi; Wheat, C. Geoffrey; You, Chen-Feng
Abstract: Compositional changes, dehydration reactions and fluid flow in subducted sediments influence seismogenesis and arc magmatism in subduction zones. To identify fluid flow and water–rock interaction processes in the western Nankai Trough subduction zone (SW Japan) we analyzed boron concentration and boron isotope composition (δ 11 B) of pore fluids sampled across the subduction zone forearc from depths of up to ∼922 m below seafloor during four Integrated Ocean Drilling Program (IODP) Expeditions. The major structural regimes that were sampled by coring include: (1) sedimentary inputs, (2) the frontal thrust zone, (3) the megasplay fault zone, and (4) the forearc basin. From mass balance consideration we find that consumption of boron (B) by ash alteration and desorption of B from the solid phase, mediated by organic matter degradation, produces a net decrease in B concentrations with depth down to ∼120 μM and variable δ 11 B values in the range of ∼+20‰ and +49‰. Interstitial water in sediments on the incoming oceanic plate are influenced by more efficient mobilization of exchangeable B from the solid phase due to higher temperatures and alteration of the oceanic crust that acts as a sink for 10 B. At the tip of the megasplay fault zone, elevated B concentration and B isotopic composition suggest that underthrust coarse-grained slope sediments provide a pathway for fluids out of the upper (<2 km) accretionary prism. Silt and sand layers in the underthrust section of the downgoing plate favor fluid escape in seaward direction from depths equivalent to the temperature range of 60–150 °C. At both locations the δ 11 B signature evolves during updip migration through re-adsorption. Mass balance considerations suggest a shallower fluid source depth compared to pore fluids sampled previously near the décollement zone along the central portion of the Nankai margin.